2019
DOI: 10.1016/j.jpsychires.2018.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Implications of de novo mutations in guiding drug discovery: A study of four neuropsychiatric disorders

Abstract: Recent studies have suggested an important role of de novo mutations (DNMs) in neuropsychiatric disorders. As DNMs are not subject to elimination due to evolutionary pressure, they are likely to have greater disruptions on biological functions. While a number of sequencing studies have been performed on neuropsychiatric disorders, the implications of DNMs for drug discovery remain to be explored.In this study, we employed a gene-set analysis approach to address this issue. Four neuropsychiatric disorders were … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 93 publications
0
2
0
Order By: Relevance
“…Exome sequencing of schizophrenia probands and their unaffected parents has uncovered de novo rare variation (spontaneously occurring in the proband) mapped to retinoid genes which could be clinically significant for that individual [99]. Genes enriched for predicted deleterious de novo rare variation in schizophrenia were also overrepresented for genes which interact with at-RA [100]. Whole genome sequencing (WGS) provides an opportunity to more accurately assess the impact of rare variants in schizophrenia.…”
Section: Genomic Characterisation Of Retinoid Dysregulation In Schizomentioning
confidence: 99%
“…Exome sequencing of schizophrenia probands and their unaffected parents has uncovered de novo rare variation (spontaneously occurring in the proband) mapped to retinoid genes which could be clinically significant for that individual [99]. Genes enriched for predicted deleterious de novo rare variation in schizophrenia were also overrepresented for genes which interact with at-RA [100]. Whole genome sequencing (WGS) provides an opportunity to more accurately assess the impact of rare variants in schizophrenia.…”
Section: Genomic Characterisation Of Retinoid Dysregulation In Schizomentioning
confidence: 99%
“…Also, while the focus of this review is on repositioning using GWAS data, the pathway-based approach can be readily extended to handle other types of human genomic data. For example, a recent study showed by pathway analysis that de novo mutations may be used to guide drug discoveries for neuro-psychiatric disorders [64]. Readers may also refer to [65] for further discussions on the potential of GWAS data in drug discovery for neuro-psychiatric disorders.…”
Section: Drug Repositioning Based On Pathway or Gene-set Analysismentioning
confidence: 99%